Sami Is a Critical Thinker, but He Is a Striving Reader - فهد بن عبدالله ماشع الحربي الحربي (Faculty of Education - Port Said University, 2022)
The aim of this case study is to find how an ESL striving reader can tap into critical thinking and language strategies when working to comprehend narrative and expository texts in a second language. A ten-year-old child, Sami, came from Saudi Arabia six months before meeting the researcher. He was frustrated because his English skills were at a low level, and in particular, because he could speak and read Arabic fluently. Therefore, the researcher wanted to use the skills Sami had as a fluent reader in his first language to assist in teaching him a second language. The researcher determined four strategies that the student could master in his first language and then in his second language. The plan includes more than twenty sessions, and before the sessions started, the student was given a pre-test, and after finishing the sessions, a post-test. The results show that the student's comprehension was improved after finishing the interventions.